Couple interaction and child social competence: The role of parenting and attachment. Issue 2 (25th September 2018) - Neppl, Tricia K.; Wedmore, Haley; Senia, Jennifer M.; Jeon, Shinyoung; Diggs, Olivia N.
Abstract: The current study examined the association between positive couple interaction and child social competence as mediated through positive parenting and parent–child attachment security. Prospective, longitudinal data came from 209 mothers, fathers, and their biological child. Information regarding observed positive couple interaction, observed positive parenting, and parent–child attachment security were assessed when the child was 2–4 years old, and child social competence was assessed at 5 years old. Mothers and fathers were analyzed separately in the model. Results indicated that for both mothers and fathers, positive couple interaction was indirectly associated with child social competence through positive parenting and parent–child attachment. These pathways remained statistically significant even after child social competence at age 2–4 was taken into account. Results suggest that couple interaction spills over into parenting which impacts parent–child attachment, which is associated with positive child developmental outcomes.